PENGEMBANGAN MEDIA ENGLISH VOCABULARY CARD UNTUK MENINGKATKAN MINAT BELAJAR BAHASA INGGRIS DI MI TA’LIMUL HUDA BUGOHARJO LAMONGAN - Rosyidatul Kholidah, Dwi; Nadhifah, Arin (Ibriez : Jurnal Kependidikan Dasar Islam Berbasis Sains, 2023)
The development of English vocabulary card learning media is one of the media that can help teachers during the learning process and help increase students' interest in learning. The reality on the ground shows that when learning takes place there is no supporting media, students have difficulty memorizing vocabulary because writing and reading are different, especially students' lack of interest in learning English. The purpose of this development is to produce products in the form of learning media, namely English vocabulary card media that are fun, not boring, interesting and have high interest in learning English. This can make it easier for students to memorize vocabulary with the theme Part Of Body. This type of research uses research and development or what is called Research and Development, which follows the ADDIE research model developed by Dick and Carry. With the results of the material/content expert validation test results of 82%, the media/design validation test results 90%, the linguist validation test results 82%, the results of the learning practitioner experts at 86% and the student respondents' questionnaire results by 91%. From these results it can be stated that it is feasible to be used as a learning medium. Based on the results of the question activity 2 in the LKS, the pre-test got an average score of 46 and the post-test got an average score of 86. This can be concluded by using the English vocabulary card media, students' interest in learning is high and learning outcomes students increase.